Effectiveness of Peduli Family Module to Engage Diet, Exercise, and Medication Adherence on Type 2 Diabetes - Ni Wayan Trisnadewi; Ni Putu Wiwik Oktaviani; Ni Komang Ayu Resiyanthi (Public Health of Indonesia)
Background:For diabetes patients, adhering to lifelong self-care routines is a significant challenge.